Main characteristics of African cities - (:unkn) unknown (My University, 2022)
Africa, which entered late in the urbanization process, is the most rural continent, but one that is urbanizing rapidly. This poorly controlled urban growth leads to disproportionate growth of cities because the increase in the number of African millionaire cities raises increasingly acute social questions, questions of planning and management of spaces. This article, based on documentary research, therefore aims to study the main characteristics of large African cities. Overall, it emerges from this theoretical study that African cities are characterized in addition to rapid urbanization, migration increasingly linked to poverty in rural areas; informality, colonial heritage and especially urban macrocephaly and bicephaly.
Keywords: African Research